Negotiating railroad safety in the late Ottoman Empire: The state, railroad companies, trainmen, and trespassers. (May 2019) - Nacar, Can
Abstract: This study examines different approaches taken in the late Ottoman Empire to deal with the risks and dangers posed by railroads. Like its counterparts in Europe and the United States, the Ottoman state actively sought to protect individuals against railroad risks. For this purpose, it mandated the use of certain devices meant to facilitate the safe flow of railroad traffic and introduced measures that aimed to discipline railroaders and pedestrians into behaving appropriately. However, the state was not the only actor that struggled to address railroad risks. Railroad companies, primarily to advance their economic interests, incorporated technologies that considerably reduced the risk of collisions. Yet economic concerns also sometimes hampered investments in railroad safety. For instance, the manner in which trespassing cases were handled by accident investigation committees and courts allowed the companies to avoid their obligations with respect to fencing around railroad tracks. As a result, it was easy for pedestrians to use tracks near their homes and workplaces as pathways. Finally, the article also shows that in performing their duties, trainmen enjoyed considerable freedom from control by railroad managers. This freedom was further reinforced by the shortage of experienced and skilled labor in the Ottoman railroad industry.